2022
DOI: 10.23910/1.2022.2640
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Correlation and Path-Coefficient Studies in Litchi (Litchi chinensis Sonn.) for Plant Growth, Panicle and Yield Attributes

Abstract: Studies were carried out in National Active Germplasm Site (NAGS) at ICAR-NRC on Litchi, Muzaffarpur, Bihar, India during 2018 and 2019 to find out the association between different characters and magnitude of association of different characters with yield (kg plant-1) in nine clones of litchi (Litchi chinensis Sonn.). Result revealed that genotypic coefficient were higher than their corresponding phenotypic ones implying an inherent relationship among them. The differences between genotypic and phenotypic coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
(7 reference statements)
2
5
0
Order By: Relevance
“…High values of heritability for the traits clarified that they were least affected by environmental modification and selection based on phenotypic performance would be reliable. Similar findings were also reported by several workers (Srivastava et al 2014, Lal et al 2022 who reported high heritability with high genetic gain for different attributes in other fruits crops. It may be concluded that higher values of both PCV and GCV for various traits such as tree volume, leaf area and leaf thickness indicate that more improvement can be achieved by selection based on these traits.…”
Section: Resultssupporting
confidence: 91%
“…High values of heritability for the traits clarified that they were least affected by environmental modification and selection based on phenotypic performance would be reliable. Similar findings were also reported by several workers (Srivastava et al 2014, Lal et al 2022 who reported high heritability with high genetic gain for different attributes in other fruits crops. It may be concluded that higher values of both PCV and GCV for various traits such as tree volume, leaf area and leaf thickness indicate that more improvement can be achieved by selection based on these traits.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, Singh et al (1999) has reported that the genetic characteristics of leaf is an essential parameter which will help in identi cation and classi cation of litchi cultivars. Similarly, the ndings of this study are in accordance with Lal et al (2022) and Lal et al (2023) for qualitative traits in litchi. However, above studied these qualitative traits can be utilized e ciently for identi cation and discrimination of longan genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…Arora et al (1996) have also reported signi cant variability in litchi genotypes with regard to fruit, aril, and seed characters at different locations. The variation observed among the litchi genotypes were might be due to the genetic make-up of plant (Lal et al, 2022); nutrition and climatic conditions (Cronje et al, 2009). Wall (2006) has reported that the same cultivar of longan may differ in ascorbic acid and TSS at different locations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations